How does prednisolone work in pemphigus? - A. Grando, Sergei (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2004)
In this review the mechanism of action of glucocorticosteroids (GH) in pemphigus is discussed. In pemphigus, GH may work by: (i) inhibiting antibody synthesis; (ii) suppressing inflammation, especially eosinophilic spongiosis; and (iii) stopping acantholysis via a direct pharmacological effect on keratinocytes. The anti-acantholytic effects of methylprednisolone include upregulation of gene expression of adhesion molecules and protection of keratinocyte adhesion molecules from antibody-induced phosphorylation. Experimental drugs, such as lazaroids that are deprived of the mineralocorticoid and glucocorticoid effects of GH, should be tested for their ability to replace GH in the treatment of pemphigus.